Biodegradation of phenol by cold-adapted bacteria isolated from antarctic soils - Lee, Gillian Li Yin (2018)
Phenol is an important pollutant widely discharged as a component of hydrocarbon fuels, but its degradation in cold regions is a great challenge due to the harsh environmental conditions. To date, there is little information available concerning the biodegradation of phenol by indigenous Antarctic bacteria. This study addresses the isolation of three phenol-degrading bacterial strains from King George Island, Antarctica. Based on preliminary screening, three isolates (AQ5-05, AQ5-06, and AQ5-07) capable of completely degrading 0.5 g/L phenol within 120 h at 10°C were selected for detailed study. Two were identified as Arthrobacter spp., and one as Rhodococcus sp., based on 16S rRNA sequences. All strains were non-motile, Gram-positive, oxidase-negative and catalase-positive. A study on the effects of parameters including temperature, pH, salinity and nitrogen source was conducted to optimise the conditions for phenol degradation using one-factor-at-a-time (OFAT) and response surface methodology (RSM). Based on the results from OFAT, AQ5-05 showed highest phenol degradation at 15°C, pH 7.5, 0.1 g/L NaCl and 0.4 g/L (NH4)2SO4, AQ5-06 achieved maximum phenol degradation at 10°C, pH 7.5, 0.1 g/L NaCl and 0.3 g/L (NH4)2SO4 while optimum phenol degradation for AQ5-07 was observed at 10°C, pH 7.0, 0.15 g/L NaCl and 0.3 g/L (NH4)2SO4. Statistical analysis of the results obtained from RSM showed improvement in phenol degradation for all strains compared to the conventional OFAT approach. All strains showed optimum pH of 7.0 as optimised using RSM, with maximum phenol degradation observed under slightly different combinations of conditions for each: 17.5°C for AQ5-05, 10°C and 0.1 g/L of NaCl for AQ5-06, and 12.5°C and 0.4 g/L of (NH4)2SO4 for AQ5-07. In addition, enzyme activities, and genes encoding phenol degradative enzymes identified using whole genome sequencing (WGS), were investigated to determine the pathways of phenol degradation. Complete phenol degradative genes involved in only ortho-cleavage were detected in all three strains and the results were revalidated using enzyme assays of catechol 1,2-dioxygenase and catechol 2,3-dioxygenase. The data obtained indicated activity of only catechol 1,2-dioxygenase in all three strains, in agreement with the results from WGS. Graphical and statistical analyses on the growth kinetic models used indicated that the best models were Luong models for strains AQ5-05 and AQ5-07, while the best model for strain AQ5-06 was the Han-Levenspiel model. Meanwhile, the calculated values for maximum growth rate (μmax), half saturation constant for maximum growth (Ks), maximum concentration of substrate tolerated (Sm) and empirical constant (n) were 0.180 h-1, 0.390g/L, 1.290g/L and 0.240 for strain AQ5-05, and 0.175 h-1, 0.388 g/L, 1.287 g/L and 0.236 for strain AQ5-07, respectively, according to the Luong equation. For strain AQ5-06, the Han-Levenspiel equation gave the values of μmax, Ks, Sm with empirical constants m and n of 0.077 h-1, 0.364 g/L, 1.273 g/L, 1.879 and 2341.00, respectively. All isolated strains were psychrotolerant with the optimum temperature for phenol degradation between 10 and 15°C. This study suggests the potential use of cold-adapted bacteria in the bioremediation of phenol over a wide range of low temperatures.